MEMBANGUN KESADARAN SAFETY AND SMART RIDING MAHASISWA FEB UNDARIS KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Dharma Ayu, Pitaloka; Suryatama, Fajar; Nurmiyati, Nurmiyati (Tahta Media Grup, 2025)
The number of traffic accidents has continued to increase from year to year, which is certainly very concerning. Human error remains the main cause of traffic accidents, while traffic awareness should be the responsibility of all members of society. Changing the mindset regarding the lack of traffic awareness is not an easy task; it requires persistence, seriousness, and continuity. The Community Service Team of FEB Undaris strives to contribute to building traffic awareness among FEB Undaris students through a Safety Riding and Smart Driving socialization program, by presenting certified experts in smart and defensive driving training. This community service activity was carried out through the presentation of Safety Riding and Smart Driving materials and class-based discussions using a qualitative approach with the on-class method, targeting students of the Faculty of Economics and Business, Undaris, in Semarang Regency. The program was held at the HM Mansur Auditorium, Undaris, Semarang Regency.